A formação de professores para a educação do campo na perspectiva de Paulo freire - Marmet, Rosely Rodrigues de Bessa (2024)
Rural Education plays a crucial role in providing quality and relevant education to rural populations. In this context, teacher training for this area needs to be anchored in a solid theoretical basis that is believed to be found in the work of Paulo Freire. This dissertation seeks to examine the problems faced in rural education, such as the devaluation of local knowledge, the conditions resulting from deficient education that does not meet the specific needs of communities, as well as the lack of a pedagogical approach that values ​​local culture and encourages the active participation of students from these locations in their education. This raises the guiding questions of this research: how can inclusion be promoted in Rural Education through teacher training from Paulo Freire's perspective, considering the sociocultural, economic and geographic particularities of rural communities? What is the impact of teacher training from Paulo Freire's perspective on Rural Education? The general objective is to understand and reflect on teacher training in Rural Education based on Paulo Freire's perspective. The specific objectives aim to identify the historical origins of rural schools, map social movements related to rural education and analyze the impacts of the actions of these movements. The dissertation is divided into three chapters. The first chapter provides an overview of the historical context, presenting the struggle of rural school movements, the regional Rural Education curriculum, the discussions that served as the basis for the movement of these rural schools, as well as the political milestones of their implementation on a new Rural Project and Rural Education. The second chapter revisits Freire's assumptions pertinent to Rural Education, which are fundamental for an approach committed to the reality of students and to social transformation. This approach explains an education that starts from the students' reality, that values ​​their knowledge, experiences and culture and that helps them to actively engage in the learning process. The third chapter addresses the challenges faced by rural education teachers, both in their initial training and in their ongoing training. It is concluded that teacher training, from Paulo Freire's perspective, strengthens the rural education approach by enabling them to promote dialogue, awareness and social transformation in rural communities, thus contributing to a more inclusive and fair education.